Short Video Entrepreneurship among Smallholder Farmers in the Era of Digital Intelligence: An Exploration of Labour Alienation - Yuying Li (Journal of Asian Social Science Research, 2024)
This article deals with smallholder farmers in L village who engaged in short-video entrepreneurship on less than 50 acres of farmland. Through a digital labour alienation perspective and in-depth interviews, it was discovered that these farmers faced issues such as the transfer of ownership of their labour products, the standardization of labour processes, and a sense of alienation from their own human identity. These disparities stem primarily from the inequalities of digital power, driven by factors like data indicators, algorithm manipulation, inequitable agreements, re-intermediate exploitation, and identity psychology. By examining specific digital labour practices in this context, this research provides a more comprehensive understanding of worker alienation in the digital labour space. The findings have significant value and practical importance for enhancing the effectiveness of new media in revitalizing rural communities.